IMPLEMENTATION OF COMMUNITY RIGHTS IN VILLAGE DEMOCRACY - Mukhammad Soleh; Dian Utami Ikhwaningrum; Marsudi Dedi Putr; Vivi Fauziatul Aini; Angellica Chirzt Ernestacia (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The community has the right to express aspirations, suggestions, and opinions in the village government's execution. The goal of this study is to examine how community rights are implemented and identify barriers to their effective execution in village management. In particular, the preparation of the Draft Village Regulation aims to enhance the implementation of democracy in the Village. The research method employed is empirical legal research, utilizing primary and secondary data collection methods through in-depth observations and interviews. The results are based on field studies and documents from the Gunungsari Village Government, Tajinan District, Malang Regency. A qualitative juridical analysis is then carried out. The study's results show that implementing community rights in expressing aspirations, suggestions, and opinions is crucial in preparing the draft village regulations. In the planning activities for preparing village regulations, participation has been carried out through village deliberations and hamlet deliberations, which have identified inhibiting factors. First, there are still people who do not understand their rights. Second, there are still people who remain indifferent. Third, the community has not been informed about the village authority's plan to create village ordinances. Techniques for conquering difficulties 1). connecting the community's and the village government's perspectives, goals, and tactics. 2) Budgetary support from the village government for improving community human resources through education, training, and courses. 3) Village government programs and activity plans must be oriented towards improving community income and welfare. 4) Improved facilities and infrastructure for disseminating plans for drafting village regulations.